CTLA‐4 and CD28 genes' polymorphisms and renal cell carcinoma susceptibility in the Polish population – a prospective study. Issue 5 (25th September 2015) - Tupikowski, K.; Partyka, A.; Kolodziej, A.; Dembowski, J.; Debinski, P.; Halon, A.; Zdrojowy, R.; Frydecka, I.; Karabon, L.
Abstract Polymorphisms in co‐stimulatory genes are associated with susceptibility to several malignances such as breast cancer, cervical cancer and chronic lymphocytic leukemia, but have been scarcely investigated in renal cell cancer (RCC). A total of 310 RCC patients and 518 controls were genotyped for single‐nucleotide polymorphisms (SNPs) in the CTLA‐4 and CD28 genes: CTLA‐4c.49A>G (rs231775), CTLA‐4g.319C>T (rs5742909), CTLA‐4g.*6230G>A (CT60; rs3087243), CTLA‐4g.*10223G>T (Jo31; rs11571302), CD28c.17+3T>C (rs3116496) and CD28c.‐1042G>A (rs3181098). The distribution of the alleles, genotypes and haplotypes in the CTLA‐4 and CD28 genes were similar in the RCC patients and in the controls. However, among the patients with a clear cell RCC (CCRCC), the G allele carriers of CT60 and Jo31 SNPs were overrepresented, and the overrepresentation became significant for the carriers of CT60[G] allele in CCRCC patients with necrosis in the primary tumor (P = 0.046). The CTLA‐4c.49A>G[A]/CTLA‐4g.319C>T[C]/CT60[A]/Jo31[T]/CD28c.17+3T>C[T]/ CD28c.1042G>A[G] haplotype was associated with an approximately threefold increased risk of primary tumor necrosis in CCRCC patients (Pcorrected = 0.0000007) and with the advanced stage of disease (IV) (Pcorrected = 0.001). When stratified by gender, CD28c.‐1042G>A[GG] genotype was more frequent in the female CCRCC patients compared with healthy women (P = 0.042). Polymorphisms in the CTLA‐4 and CD28 genes, in particular considered together as haplotypes, were associated with increased risk of CCRCC, especially with necrosis and with the advanced stage of disease. The CD28c.‐1042G>A SNP modulates the risk of CCRCC in women. These findings indicate that the associations of the CTLA‐4 and CD28 polymorphisms with the risk of renal cancer are worth further study in a larger group of patients.